The Impact of Community Social Changes on the Digitalization of the Implementation of Stock Waqf - Rodotun Nimah (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Abstract The practice of cash waqf, especially stock waqf, in the last 5 years in Indonesia has increased in addition to other cash waqf. This is the impact of increasingly sophisticated digitalization developments that affect people's mindsets. Stock waqf is a new innovation because waqf through money is considered to have a more flexible nature to make new breakthroughs according to the needs of the times without reducing the essence of the waqf. Waqf shares are usually intended for productive social purposes or investments, the results of which are for the benefit of the people. The public or entrepreneurs are more interested in stock waqf because it can be channeled directly through nadzir waqaf and is easy to access. In general, the model for implementing stock waqf is derived from profits management of shares which are then given to waqf management institutions for then add to the benefits of waqf in the form of productive assets as well as physical assets that are useful for social.This research is a library research using a sociological approach. The type of research used is qualitative research using documentation data collection techniques and then analyzed by reducing data, presenting data and then drawing a conclusion. So that innovation in the form of cash waqf in Indonesia due to the positive impact of social changes in society is known comprehensively and has a strong legal basis. Keywords: Impact of Change, Social Society, Digitization, Stock Waqf.